2009
DOI: 10.1111/j.1600-0765.2008.01170.x
|View full text |Cite
|
Sign up to set email alerts
|

Stretching stimulates fibulin‐5 expression and controls microfibril bundles in human periodontal ligament cells

Abstract: These results suggest that fibulin-5 up-regulated in response to tension strain may control the formation of microfibril bundles in periodontal ligament.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 17 publications
1
14
0
1
Order By: Relevance
“…We showed previously that fibulin-5 localizes with oxytalan fibers to control their coalescence [16]. In the present study, we showed by immunoprecipitation that EMILIN-1 colocalizes with fibrillin-1.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…We showed previously that fibulin-5 localizes with oxytalan fibers to control their coalescence [16]. In the present study, we showed by immunoprecipitation that EMILIN-1 colocalizes with fibrillin-1.…”
Section: Discussionsupporting
confidence: 71%
“…An ultrastructural study of EMILIN-1 immunolocalization revealed that the molecule was clearly labeled in oxytalan fibers of the corneal stroma [13]. Moreover, based on the fact that EMILIN-1 can bind with fibulin-5, which is expressed on oxytalan fibers in our PDL culture model [15,16], we hypothesized that EMILIN-1 might contribute to the formation of oxytalan fibers in PDL. In the present study, we used a culture model of pure microfibrils to investigate the role of EMILIN-1 in the development of oxytalan fibers and found that EMILIN-1 colocalizes with oxytalan fibers and regulates their biogenesis.…”
Section: Introductionmentioning
confidence: 89%
“…Functional strain has been shown to induce coalescence of oxytalan fibers in cultured PDL fibroblasts [9]. By means of the gene silencing technique, we have demonstrated that fibulin-5, upregulated upon exposure to stretching stress, is a key molecule for the induction of oxytalan fiber coalescence [10]. Fibulin-5 is also known to be a crucial molecule in the control of elastic fiber formation [11,12].…”
Section: Introductionmentioning
confidence: 94%
“…PDL fibroblasts were isolated from three different donors and cultured, as described previously [10]. Briefly, connective tissues were obtained surgically from the PDL of premolar teeth extracted for orthodontic reasons.…”
Section: Cells and Culturementioning
confidence: 99%
“…PDL cell culture and migration assay PDL fibroblasts were isolated from a donor and cultured, as described previously 23) . Culture medium for PDL fibroblasts was supplemented with 10 % newborn calf serum (NCS; Invitrogen, Carlsbad, CA, USA) and 100 units/ml penicillin and 100 µg/ml streptomycin (Roche Diagnostics, Mannheim, Germany) at 37 °C in humidified air containing 5 % CO 2 .…”
Section: Section Preparation and Immunohistochemistrymentioning
confidence: 99%